2014
DOI: 10.1039/c3nj01560b
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular luminescent hydrogels based on β-amino acid and lanthanide ions obtained by self-assembled hydrothermal reactions

Abstract: Hydrothermal synthesis of four new supramolecular hydrogels based on lanthanide ions with promising properties for RGB systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Huang et al also found that the color of the emission of a lanthanide–cholate hydrogel depends on different lanthanide ions or codoping ions. 454 Utilizing the iminodiacetic acid ( 161 ) as a ligand to coordinate with lanthanides, Alves et al 455 prepared a series of hydrogels with the lowest CGC value at 0.04 wt %. Banerjee et al 456 designed a series of tyrosine-based amphiphiles ( 162 ) which bind with Ni 2+ ion selectively and result in hydrogels at CGC values of 0.78, 0.75, and 0.63 wt % when the chain length is 10, 12, and 14, respectively.…”
Section: Molecular Designmentioning
confidence: 99%
“…Huang et al also found that the color of the emission of a lanthanide–cholate hydrogel depends on different lanthanide ions or codoping ions. 454 Utilizing the iminodiacetic acid ( 161 ) as a ligand to coordinate with lanthanides, Alves et al 455 prepared a series of hydrogels with the lowest CGC value at 0.04 wt %. Banerjee et al 456 designed a series of tyrosine-based amphiphiles ( 162 ) which bind with Ni 2+ ion selectively and result in hydrogels at CGC values of 0.78, 0.75, and 0.63 wt % when the chain length is 10, 12, and 14, respectively.…”
Section: Molecular Designmentioning
confidence: 99%
“…To date, there have been several reports in the literature on lanthanide-ion-based metallogels. Holten-Andersen and co-workers reported white-light-emitting multistimuli-responsive lanthanide-ion-based metallogels. , Alves Jr. and co-workers reported β-amino acid- and lanthanide-ion-based supramolecular luminescent hydrogels . Maitra et al demonstrated facile metallogel formation of several lanthanide­(III) cholates .…”
Section: Introductionmentioning
confidence: 99%
“…50,58 Alves Jr. and co-workers reported β-amino acid-and lanthanide-ion-based supramolecular luminescent hydrogels. 59 Maitra et al demonstrated facile metallogel formation of several lanthanide(III) cholates. 60 Among different lanthanides, terbium has earned a special place due to its versatile applications, such as in magnetic devices, 61 electroluminescence, 62 biological fields, 63 optical devices, 64 time-resolved fluoro-immuno assay, 65 luminescence imaging, 66 and sensing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7,14,15 Recently, we demonstrated a novel class of photochromic hydrogels obtained from lanthanide oxides (Ln 2 O 3 ) and iminodiacetic acid (H 2 IDA). 16 These eco-friendly lanthanide-organic gels (LOGs) were easily obtained hydrothermally under soft conditions, using only a few reagents at low temperatures without the need for any organic solvent. Even so, they presented remarkable optical properties in the visible region provided by the Eu 3+ and Tb 3+ ions.…”
Section: Introductionmentioning
confidence: 99%